Incidence and Factors Associated With Major Amputation in Patients With Peripheral Artery Disease: Insights From the EUCLID Trial. Issue 7 (July 2020) - Long, Chandler A.; Mulder, Hillary; Fowkes, F. Gerry R.; Baumgartner, Iris; Berger, Jeffrey S.; Katona, Brian G.; Mahaffey, Kenneth W.; Norgren, Lars; Blomster, Juuso I.; Rockhold, Frank W.; Hiatt, William R.; Patel, Manesh R.; et al.
Abstract : Background: Peripheral artery disease (PAD) is associated with increased risk of mortality, cardiovascular morbidity, and major amputation. Data on major amputation from a large randomized trial that included a substantial cohort of patients without critical limb ischemia (CLI) have not been described. The objective was to describe the incidence and types of amputations in the EUCLID trial (Examining Use of Ticagrelor in Peripheral Artery Disease) population, subcategorize amputations in the CLI versus no CLI cohorts, and describe the events surrounding major amputation. Methods and Results: Postrandomization major amputation was analyzed in the EUCLID trial. Patients were stratified by baseline CLI status. The occurrence of major amputation was ascertained and defined as the highest level. Perioperative events surrounding major amputation were obtained including acute limb ischemia, revascularization, and all-cause mortality. All variables were assessed for significance in univariable and multivariable models. The rate of major amputation during the course of the trial was 1.6% overall, 8.4% in the CLI at baseline group, and 1.2% in the no CLI at baseline group. The annualized rate of major amputation was 0.6% in PAD overall, 3.9% in the CLI at baseline group, and 0.5% in the no CLI at baseline group. Several factors were associated with increased risk of major amputation, including history of amputation, the presence of diabetes mellitus, baseline Rutherford category 4 to 6, and an ankle-brachial index <0.8. Factors associated with a lower risk for major amputation included prior statin use. The 30-day mortality rate after major amputation was 6.5% overall, 5.6% in the CLI at baseline group, and 6.8% in the no CLI at baseline group. The annual mortality rate following major amputation was 22.8% in the CLI at baseline group and 16.0% in the no CLI at baseline group. Conclusions: The risk factors for major amputation in EUCLID patients are similar to previous large registries' reports except for diabetes mellitus in patients with CLI. The mortality following major amputation is lower in the EUCLID trial compared with registry data. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01732822.